Business planning for unintended consequences - good intentions are not enough. (2016) - Mortimer, Genevieve
Unintended consequences are at the heart of a dilemma for firms acting on corporate sustainability. On the one hand, corporate sustainability encourages businesses to take bold, timely and ethical action to address society's grand challenges. On the other, due to the complexity and unpredictability of our world, action brings with it a higher risk of unintended consequences. This paper makes the case that unintended consequences are real and an important consideration for businesses taking action to improve their sustainability in complex environments. This paper develops a framework which positions unintended consequences among other business concepts. Further, I demonstrate fear of unintended consequences is a challenge that can further hinder corporate action on sustainability. However, developing tools and processes to detect unintended consequences, learn from them and respond innovatively provides an opportunity for businesses to better manage in uncertain and complex environments. This paper demonstrates why, in a complex world, a strategy for unintended consequences is needed to empower action on corporate sustainability strategy.